PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Y. Arif Christianto, 14.05.52.0234; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effect of financial performance on stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX).In this study, the sample was determined using purposive sampling with the observation period 2014 - 2016 with the number of samples obtained as many as 55 companies per year. The influence between variables is explained using multiple linear regression method with SPSS program. The type of data used is secondaryThe results showed that Current Ratio (CR), Dept to Equity Ratio (DER) had no significant negative effect on stock prices, Total Asset Turnover Ratio (TATO) had a significant negative effect on stock prices, Return on Equity (ROE) had no significant positive effect on prices. stocks, Earning Per Share (EPS) has a significant positive effect on stock prices Keywords: Current Ratio (CR), Dept to Equity Ratio (DER), Total Asset Turnover Ratio (TATO), Retun On Equity (ROE), Earning Per Share (EPS), Stock Price